At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To solve the quadratic equation \( (-x^2 + 2x + 77 - 80) = 0 \) that simplifies to \( x^2 - 2x - 3 = 0 \), let's follow these steps closely:
1. Identify the quadratic equation:
The given equation is \( x^2 - 2x - 3 = 0 \).
2. Solve the quadratic equation:
To solve this quadratic equation, we look for values of \( x \) that satisfy the equation. One common method is to factorize the quadratic expression.
3. Factorize the quadratic expression:
We need two numbers that multiply to \(-3\) (the constant term) and add up to \(-2\) (the coefficient of the linear term). These two numbers are \(-3\) and \(1\). Therefore, we can rewrite the quadratic expression as:
[tex]\[ x^2 - 3x + x - 3 = 0 \][/tex]
Next, we group the terms to factor by grouping:
[tex]\[ (x^2 - 3x) + (x - 3) = 0 \][/tex]
Factor out the common terms:
[tex]\[ x(x - 3) + 1(x - 3) = 0 \][/tex]
4. Apply the zero product property:
We see that the factored form is:
[tex]\[ (x - 3)(x + 1) = 0 \][/tex]
Using the zero-product property, we set each factor equal to zero:
[tex]\[ x - 3 = 0 \quad \text{or} \quad x + 1 = 0 \][/tex]
Solving these equations gives:
[tex]\[ x = 3 \quad \text{or} \quad x = -1 \][/tex]
So, the solutions to the quadratic equation [tex]\( x^2 - 2x - 3 = 0 \)[/tex] are [tex]\( x = 3 \)[/tex] and [tex]\( x = -1 \)[/tex].
1. Identify the quadratic equation:
The given equation is \( x^2 - 2x - 3 = 0 \).
2. Solve the quadratic equation:
To solve this quadratic equation, we look for values of \( x \) that satisfy the equation. One common method is to factorize the quadratic expression.
3. Factorize the quadratic expression:
We need two numbers that multiply to \(-3\) (the constant term) and add up to \(-2\) (the coefficient of the linear term). These two numbers are \(-3\) and \(1\). Therefore, we can rewrite the quadratic expression as:
[tex]\[ x^2 - 3x + x - 3 = 0 \][/tex]
Next, we group the terms to factor by grouping:
[tex]\[ (x^2 - 3x) + (x - 3) = 0 \][/tex]
Factor out the common terms:
[tex]\[ x(x - 3) + 1(x - 3) = 0 \][/tex]
4. Apply the zero product property:
We see that the factored form is:
[tex]\[ (x - 3)(x + 1) = 0 \][/tex]
Using the zero-product property, we set each factor equal to zero:
[tex]\[ x - 3 = 0 \quad \text{or} \quad x + 1 = 0 \][/tex]
Solving these equations gives:
[tex]\[ x = 3 \quad \text{or} \quad x = -1 \][/tex]
So, the solutions to the quadratic equation [tex]\( x^2 - 2x - 3 = 0 \)[/tex] are [tex]\( x = 3 \)[/tex] and [tex]\( x = -1 \)[/tex].
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.